BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
Guava Diseases .(An annotated bibliographyÂ 1907-1990). By A.K. Misra and am Prakash. Publishers : Bishen Singh and Mahendra Pal Singh, Dehradun. 1994. pp. 132. ’Detection of Plant Pathogens and theirÂ Management’ Edited by J.P. Verma, AnupamÂ Varma and Dinesh Kumar, Angkor Publishers(P)Â Ltd., New Delhi, 1-475 pp. Prices Rs. 475. Â